Healthcare workers’ experiences with integrated HIV and TB prevention in Liangshan, China: a qualitative exploration of barriers and enablers - Bi, Ruili; Pei, Rong; Jike, Chunnong; Yu, Gang; Wang, Ju; Wang, Zhonghong; Wang, Yubin; Zhang, Xujia (Frontiers in Public Health, 2025)
BackgroundEvidence on frontline implementation of integrated HIV/TB prevention in resource-limited, ethnic minority regions remains limited. Liangshan Yi Autonomous Prefecture in Southwest China carries a dual HIV/TB burden. This study explored healthcare workers’ experiences with China’s Integrated Prevention and Control of Four Diseases (IPC4D) policy to identify barriers and enablers of service integration.MethodsA qualitative phenomenological study was conducted from July to December 2024. 37 semi-structured interviews were held with purposively sampled healthcare workers across prefectural CDCs, infectious disease hospitals, county hospitals, and township health centers. Interviews were audio-recorded, transcribed verbatim, and thematically analyzed following Braun and Clarke’s six-phase framework. Reflexive memos and triangulation across facility levels, professional roles, and ethnic groups enhanced study rigor.ResultsFour themes emerged. First, policy-driven progress: participants reported greater governmental support, increased resource inputs, and modest improvements in public awareness. Second, structural barriers: chronic underfunding of TB services, workforce shortages, and burnout weakened integration. Third, the multi-sectoral “1 + M + N + P” model—local government leadership (“1”), township centers (“M”), village doctors and maternal–child health staff (“N”), and public security departments (“P”)—expanded service reach but also generated task overload, cultural–linguistic challenges, and inter-sectoral friction. Fourth, urban–rural divergence: township providers faced more severe infrastructure gaps and patient non-adherence, often driven by stigma and financial constraints.ConclusionThe IPC4D policy demonstrates potential to reduce HIV/TB disparities in Liangshan, yet sustained progress requires dedicated TB financing, culturally competent workforce training, rational task redistribution, and stigma-reduction strategies that leverage Yi community networks. These findings provide practical insights for adapting integrated disease-control policies in other high-burden, resource-constrained settings.